2003
DOI: 10.1080/00986440302089
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index of supercritical CO 2 -ethanol solvents

Abstract: In-line analysis of refractive index is required for efficient design and monitoring of supercritical fluid extraction and precipitation processes. In the present work, a robust method has been developed based on measurements of laser beam deviation using an interferometer and image processing system. Data on refractive index of CO 2 -ethanol mixtures were obtained at pressures between 70 and 200 bar and temperatures between 308 and 363 K, for continuous flow of premixed solvents and, in addition, for equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Vice versa, a floating bubble of CO 2 was created, when the chamber was upturned and CO 2 was fed through the capillary from the bottom into the bulk solvent [2]. Next to the surface tension measureme nts Sun et al [3] also have shown the capacity of interferometer -microscopy to measure the concentratio n gradient through the diffusion layer between the drop and the bulk CO 2 . In this case the quantification of the mixture composition has been based on the dependence of the refractive index on the mixture composition.…”
Section: Mass Transfer At Supercritical Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vice versa, a floating bubble of CO 2 was created, when the chamber was upturned and CO 2 was fed through the capillary from the bottom into the bulk solvent [2]. Next to the surface tension measureme nts Sun et al [3] also have shown the capacity of interferometer -microscopy to measure the concentratio n gradient through the diffusion layer between the drop and the bulk CO 2 . In this case the quantification of the mixture composition has been based on the dependence of the refractive index on the mixture composition.…”
Section: Mass Transfer At Supercritical Conditionsmentioning
confidence: 99%
“…In contrast to the two studies mentioned above [3,4] we here focus onto the quantification of mass transport mechanisms taking place inside the drop and not in the surrounding bulk phase. In a previous study we have been able to quantify the diffusion of CO 2 into a drop of molten polymer [5].…”
Section: Mass Transfer At Supercritical Conditionsmentioning
confidence: 99%
“…There is experimental evidence that thiol tails on a metal surface are in the extended mode. For example, using IR spectroscopic and ellipsometric data, Porter et al 39 have shown that thiol tails with hydrocarbon group (-CH 2 ) greater than 9 assemble on gold surfaces in a densely packed manner with fully extended alkyl chains tilted from the surface normal by [20][21][22][23][24][25][26][27][28][29][30] o . This suggests that the Condensed Phase Model may not be the correct phenomenological model for our experimental system.…”
Section: Condensed/collapsed Phase Model (Cpm)mentioning
confidence: 99%
“…Optical techniques are noninvasive, lend themselves well to quantitative analysis, and are particularly advantageous for dynamic measurements. Laser interferometry is an important example of a technique developed in our group for SCF measurements (9)(10)(11)(12). In particular, as shown in the following sections, even the most uniform precipitation conditions with minimal nozzle back pressure are accompanied by significant gradients of both temperature and species concentration, which can obscure optical measurements in the supercritical flow.…”
Section: In Situ Analysis Of Mixing and Precipitation In Scfmentioning
confidence: 99%